Perspectives of Jaya Jusco's Employees towards the Discrimination of Transgender People in the Workplace and Their Responses / Nastahya Taufek and Sufia Laily Alias - Taufek, Nastahya; Alias, Sufia Laily (2010)
This paper explores the types of discrimination toward transgender people and the responses from the employees at Jaya Jusco, Penang. This research briefly demonstrates on how types of discrimination towards transgenderist employees will affect the responses from the employees. The population size of the employees at Jaya Jusco, Penang is 100. 100 employees were selected to fill the sets of questionnaire. The data were collected and analyzed by using Statistical Package for Social Science (SPSS) version 16.0. The research has identified which one of the types of discrimination has a major influence towards the responses of the employees in the workplace.